The Role of a firm’s mindset in international success - case study of Finnish marine industry firms - Kallio, Elisa (My University, 2013)
This thesis investigates the influence of a firm’s mindset on international success in the context of the Finnish marine industry. The study draws theoretical wisdom from organisational behaviour and strategic management literatures. The research aim set for this study was to identify and categorise existing strategic types based on mindsets found in the marine industry SMEs, and to link the influence of mindsets with success by examining the role of mindsets in a firm’s performance. Mindsets of firms were conceptualised as aggregate collections of perceptions that influence how the surrounding environment is discerned by the members of the firm. Mindsets are idiosyncratic to firms and therefore important firm-specific resources which influence decision-making and can be observed through the strategic behaviour of firms. Qualitative case study method was applied which was further supported by quantitative data on the financial performance of the ten case firms. Taxonomy based on the dimension of mindsets and prediction was developed to demonstrate four ideal types of firms identified within the marine industry. It was found that all of the case firms emphasised adaptation in their strategy while planning was emphasised to a varying degree. Moreover, two different methods of adapting were found; proactive and reactive. Firms which plan in the long-term and adapt proactively constantly investigate whether their plans are synchronous with the realities of the market; by having an open mindset, a firm’s perception of the reality of the market is enabling the firm to develop value creating strategies which are superiorly informed.This finding was supported by the financial data and led to the proposition that having an open mindset and placing a high level of emphasis on prediction may have a positive influence on international success. Also, it was proposed that concentrating only on exploiting business opportunities in the present time and not exploring any addition opportunities can have a negative influence on the firm’s performance, even if the mindset of the firm is open.